The nature of aggregate supply of New Zealand agriculture : thesis presented in partial fulfilment of the requirements for the degree of M. Agr. Sc - Johnson, Robin William Morris (Massey University, 1953)
It is a commonplace of the early stages of economics that agriculture is the typical example of an industry with an inelastic supply curve. There is a tendency to accept the concept of elasticity without really translating the meaning of the inelastic supply of aggregate output (the supply curve of the industry) into a practical realisation of the facts. Fact and theory tend to remain in separate compartments of the mind. The advanced student, however, is in a position to appreciate the elegance of economic theory when the theory of the firm is fully related to the shape of the supply curve of the industry. This thesis is principally a study in the conditions which determine the shape of the supply curve for agriculture. This involves a detailed analysis of the supply and demand conditions of the factors of production as they affect total output. Particular attention has been focussed in the past on the output conditions of agriculture in depression. The actual increase which took place in 1930-33 following a sharp fall in product prices, has prompted several writers to challenge the application of the classical theory of the firm to agriculture. This thesis, on the contrary, is an effort to show that such changes are compatible with the theory of the firm. [FROM INTRODUCTION]
Keywords: New Zealand; Agriculture; Economic aspects